'Too humble and sad': The effect of humility and emotional display when a politician talks about a moral issue. (December 2019) - D'Errico, Francesca
Humble leadership can be defined as a positive psychological feature that allows for admitting one's own limitations, being open to new ideas and giving a voice to, and recognizing the merits of, others. Humility has been associated with positive emotions, like gratitude and elevation, however it has been neglected in the political domain, seen on the contrary as the management of power. The present experimental study was aimed at exploring the possible persuasive effect of a humble politician by considering the role played by emotional display (joy, calm, sadness and anger) when the politician discusses an ethical issue (such as hosting immigration). Contrary to our expectations, humble communication elicited negative emotions and evaluations of the politician, especially when the politician exhibited a sad facial display; further, it induced in voters a state of personal distress towards immigrants, and thus a negative association with a hosting orientation.